ANALISIS BIAYA, VOLUME, LABA (BEP) BERDASARKAN PENGELOLAAN BIAYA OPERASIONAL DAN PENENTUAN HARGA POKOK PENJUALAN PADA USAHA GORENGAN AZIZAH DI JL. H.M. SAID NO. 8, SIDORAME BARAT I, MEDAN PERJUANGAN - Heldariska. S; Damai Rogate Tampubolon; Putri Patresia Siregar; Rachael Simanjuntak; Hamonangan Siallagan (Jurnal Akuntansi Kompetif, 2026)
This research aims to identify and classify the operational cost structure of Azizah's Gorengan Business based on management accounting principles, accurately calculate Cost of Goods Sold (COGS), and analyze break-even point (Break-Even Point / BEP) as the basis for business decision-making for MSME actors. The research uses a qualitative approach with a case study method. Data collection techniques are carried out through direct observation, in-depth interviews with business owners, and documentation. The cost data is classified into raw material costs, labor costs, and overhead costs, then analyzed using the Full Costing method for HPP calculation and BEP formula for cost-volume-profit analysis. Based on the analysis, the total operational costs of Azizah's Gorengan Business reached IDR 9,748,000 per month, with details: raw material costs of IDR 5,188,000, labor costs of IDR 0 (self-managed), and overhead costs of IDR 4,560,000. Cost of Goods Sold (HPP) of IDR 9,748,000 per month. BEP analysis shows that businesses need to sell at least 2,134 units of products per month (or ±71 units/day) assuming an average selling price of IDR 2,000/unit to break even. These findings indicate that comprehensive cost recording is essential to determine a rational selling price and ensure business sustainability.